2021
DOI: 10.1016/j.cjco.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Models for Cardiovascular Risk Reduction: The Heart Outcomes Prevention and Evaluation 4 (HOPE 4) Canada Pilot Study

Abstract: Background There is a gap between evidence and practice in the management of cardiovascular (CV) risk. Previous research indicated benefits from community-based, multi-faceted interventions to screen, diagnose, and manage CV risk in people with hypertension. Methods The Heart Outcomes Prevention and Evaluation 4 Canada pilot study (HOPE 4) was a quasi-experimental pre–post interventional study, involving one community each in Hamilton, Ontario and Surrey, British Columb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The most obvious intervention at this level is to broaden the availability and use of multidisciplinary care in the outpatient setting, based on both our findings and guideline recommendations. 23 In addition, the randomized Effectiveness of Brazilian Intervention to Increase Evidence Usage (BRIDGE) Cardiovascular Prevention study 20 showed that a combination of case management, feedback reports, and educational materials for physicians and patients leads to increased use of evidence-based therapies. Several current technologies also have capability to provide real-time checklists and decision aids to providers and aid in the proper documentation of important prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious intervention at this level is to broaden the availability and use of multidisciplinary care in the outpatient setting, based on both our findings and guideline recommendations. 23 In addition, the randomized Effectiveness of Brazilian Intervention to Increase Evidence Usage (BRIDGE) Cardiovascular Prevention study 20 showed that a combination of case management, feedback reports, and educational materials for physicians and patients leads to increased use of evidence-based therapies. Several current technologies also have capability to provide real-time checklists and decision aids to providers and aid in the proper documentation of important prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of well-developed cardiovascular prevention guidelines, a number of barriers appear to limit their application in clinical practice. 23 However, although guideline adherence has been evaluated among general practitioners, 17 , 18 , 19 , 20 , 21 data are limited regarding guideline adherence among cardiologists. 24 Better definition of treatment gaps among specialists may shed important light on the nature of these barriers, to help improve real-world prevention and lead to specific interventions.…”
mentioning
confidence: 99%
“…Routine consultations in primary care settings present an important opportunity to target lifestyle behaviours [1].Current UK guidelines recommend that we identify patients who are not sufficiently active and offer support to encourage behaviour change [2]. Lifestyle advice can be of particular benefit to patients with established cardiovascular disease risk factors, including physical inactivity, poor diet and obesity [3][4][5][6]. However, these factors are infrequently discussed with patients in routine practice [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hypertension is an inappropriately high blood pressure at rest and/or during activity and may be brought on by dysfunction of the ANS favoring the sympathetic rather than the parasympathetic response (Mancia & Grassi, 2014). Strategies to rebalance this response include the use of drugs, meditation, and even direct neuronal stimulation using focused lasers (Colombo et al, 2021) in addition to major lifestyle changes to diet, activity, and ameliorating stresses (Schwalm et al, 2021). We know, probably from personal experience, that major lifestyle changes are difficult and take time.…”
mentioning
confidence: 99%